PERANAN PRINSIP AKUNTANSI BERTERIMA UMUM DALAM KEPATUHAN PEDOMAN GOOD CORPORATE GOVERNANCE - Hidayat, Widi (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2008)
Generally accepted accounting principle included doctrin of  accounting are materiality, consistency, objectivity, matching, conservation and accounting assumption are economic entity, going concern, monetary unit, historical cost, periodicity, revenue recognition doctrin of accounting and accounting assumption support by good audit system of corporate governance. Regulatory the objective of system audit good corporate governance regulatory is the appreciated  of transparancy, accountability. Responsibility of information income statement corporation through the maximalization the value of the firm by shareholder wealth. Keywords :     Generally accepted accounting priciples, doctrin accounting. System audit good corporate governance.